2015
DOI: 10.1002/mbo3.268
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of capsule expression in Δlon strains of Escherichia coli by two novel rpoB mutations in concert with HNS: possible role for DNA bending at rcsA promoter

Abstract: Analyses of mutations in genes coding for subunits of RNA polymerase always throw more light on the intricate events that regulate the expression of gene(s). Lon protease of Escherichia coli is implicated in the turnover of RcsA (positive regulator of genes involved in capsular polysaccharide synthesis) and SulA (cell division inhibitor induced upon DNA damage). Failure to degrade RcsA and SulA makes lon mutant cells to overproduce capsular polysaccharides and to become sensitive to DNA damaging agents. Earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…Detailed analyses showed that the elicitation of this Ces phenotype by these rif mutations primarily stems from the downregulation of rcsA transcription. Our study also revealed the requirement of functional H-NS in the elicitation of Ces phenotype [32]. oligomerization [8].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Detailed analyses showed that the elicitation of this Ces phenotype by these rif mutations primarily stems from the downregulation of rcsA transcription. Our study also revealed the requirement of functional H-NS in the elicitation of Ces phenotype [32]. oligomerization [8].…”
Section: Discussionsupporting
confidence: 59%
“…They have suggested that the upstream region of rcsA promoter might possess bending/curved DNA region [25]. In our earlier study, we have provided evidence for the occurrence of bendable DNA region upstream of rcsA promoter through bioinformatics analyses [32]. In this study, perhaps for the first time we have given the genetic evidence that supports the presence of putative curved DNA region upstream of rcsA promoter.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Subsequently, allele specificity of rif‐nal mutations in the elicitation of this unorthodox phenotype was also reported . Most recently we have shown that one of the characteristic phenotype of Δlon mutant viz capsule over‐expression can be suppressed by two novel rif alleles ( rpoB12 and rpoB77 ) . These two rif alleles selectively down regulate the expression of rcsA coding for the positive regulator of cps genes and thus elicit capsule expression suppression (Ces) phenotype .…”
Section: Introductionmentioning
confidence: 98%